Perjanjian Perkawinan Dalam Konsep Maqashid asy-Syari’ah - Moh Subhan (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
A marriage agreement is an agreement made between a husband and wife when they are still married. Marriage agreements aim to protect the rights of each party and minimize conflict between husband and wife. However, on the other hand, there is a negative stigma that marriage agreements are considered taboo, unethical and full of individualistic and materialistic attitudes. Therefore, it is necessary to clearly understand the nature of the marriage agreement itself. This research aims to analyze the sociological basis and examine marriage agreements from the perspective of Maqashid Syari'ah. This research uses the Mashlahah theory. The research method used is normative juridical analysis, with data collection techniques through the study of documents, books, articles, magazines and dictionaries, then using the following techniques: analysis techniques, especially data simplification and data presentation and finally conclusions. The results of the first research show that the sociological basis of marriage agreements lies in the need for regulations that allow husband and wife to sign agreements as a step to minimize conflict between the two of them. Second, the marriage contract is in accordance with the principles of maqashid sharia, namely religious protection, soul protection, spiritual protection, property protection and child protection.